sCD40L Is Increased and Associated with the Risk of Gestational Diabetes Mellitus in Pregnant Women with Isolated TPOAb Positivity - Xinxin Chen; Qingyao Wang; Xiangguo Cong; Shuyi Jiang; Shuxiang Li; Qiong Shen; Lei Chen (International Journal of Endocrinology)
Background. Autoimmune disorders are associated with gestational diabetes mellitus (GDM) in pregnant women who were positive for thyroid peroxidase antibody (TPOAb). Soluble CD40 ligand (sCD40L) and soluble interleukin-2 receptor (sCD25) are abnormally expressed in autoimmune diseases and are reliable markers of inflammation. The purpose of this study was to evaluate sCD40L and sCD25 in early pregnancy and investigate their correlation with GDM and TPOAb. Methods. A total of 126 pregnant women in the first trimester were enrolled for analysis: 93 were positive for TPOAb and 33 were negative for TPOAb. Demographical and clinical data in early pregnancy were collected. A total of 123 participants underwent a 75 g oral glucose tolerance test in the second trimester. Serum sCD40L and sCD25 levels were measured by ELISA. Results. The incidence of GDM was 24.4% in pregnant women with isolated TPOAb positivity in our study. Both sCD40L and sCD25 were positively correlated with TPOAb (r = 0.476, P<0.001; r = 0.188, P<0.05). sCD40L was highest in (P<0.001) Ab-positive women with GDM group (P<0.05). After adjusting for TPOAb, age, TSH, FT4, triglycerides, and low-density lipoprotein cholesterol, multivariate logistic regression analysis showed that sCD40L was an independent risk factor for GDM in pregnant women with TPOAb positivity (odds ratio = 3.235, 95% confidence interval 1.024–10.218, P<0.05). Conclusions. About a quarter of pregnant women with isolated positive TPOAb might have GDM. sCD40L was an independent risk factor for GDM in women with isolated TPOAb positivity.